A Conversation with ChatGPT about Digital Leadership and Technology Integration: Comparative Analysis Based on Human-AI Collaboration - Karakose, Turgut; Demirkol, Murat; Yirci, Ramazan; Polat, Hakan; Ozdemir, Tuncay Yavuz; Tulubas, Tijen (Mdpi, 2023)
Artificial intelligence (AI) is one of the ground-breaking innovations of the 21st century that has accelerated the digitalization of societies. ChatGPT is a newer form of AI-based large language model that can generate complex texts that are almost indistinguishable from human-generated text. It has already garnered substantial interest from people due to its potential utility in a variety of contexts. The current study was conducted to evaluate the utility of ChatGPT in generating accurate, clear, concise, and unbiased information that could support a scientific research process. To achieve this purpose, we initiated queries on both versions of ChatGPT regarding digital school leadership and teachers' technology integration, two significant topics currently discussed in educational literature, under four categories: (1) the definition of digital leadership, (2) the digital leadership skills of school principals, (3) the factors affecting teachers' technology integration, and (4) the impact of digital leadership on teachers' technology integration. Next, we performed a comparative analysis of the responses generated by ChatGPT-3.5 and ChatGPT-4. The results showed that both versions were capable of providing satisfactory information compatible with the relevant literature. However, ChatGPT-4 provided more comprehensive and categorical information as compared to ChatGPT-3.5, which produced responses that were more superficial and short-cut. Although the results are promising in aiding the research process with AI-based technologies, we should also caution that, in their current form, these tools are still in their infancy, and there is a long way to go before they become fully capable of supporting scientific work. Meanwhile, it is significant that researchers continue to develop the relevant knowledge base to support the responsible, safe, and ethical integration of these technologies into the process of scientific knowledge creation, as Pandora's box has already been opened, releasing newer opportunities and risks to be tackled.
Keywords: digital leadership; technology integration; school leadership; ChatGPT; artificial intelligence; generative AI; AI in education; chatbot